The use of the Snake Ladder Board Physical Education to enhance the physical literacy of elementary students - Fina Junianti; Selvi Atesya Kesumawati; Dewi Septaliza; Bayu Hardiyono; Aprizal Fikri; Selvi Melianty; Muslimin Muslimin; Husni Fahritsani (Sriwijaya Journal of Sport, 2026)
Research Problems: Innovative instructional media are needed to enhance student engagement and promote physical literacy in elementary Physical Education (PE). Board game-based learning offers an interactive approach that integrates cognitive, affective, and psychomotor learning experiences while increasing students’ motivation and participation. Research Objectives: This study aimed to develop and validate a Physical Education learning medium in the form of the Snake Ladder Board Physical Education (SLBPE) game for elementary school students. Specifically, the study sought to determine the content validity of the developed media and examine its potential to support physical literacy by integrating fundamental movement skills, health-related knowledge, and positive learning behaviors into PE instruction. Methods: This study employed a Research and Development (R&D) design using the ADDIE model, consisting of the analysis, design, development, implementation, and evaluation phases. Data was collected using structured questionnaires administered to expert validators. Content validity was evaluated through expert judgment using the Content Validity Ratio (CVR) and Content Validity Index (CVI). The validation process involved instructional media experts, Physical Education pedagogy experts, and experienced Physical Education teachers. Results: The content validation indicated that the SLBPE learning media met the required validity standards. The average CVR value was 0.34, which falls within the acceptable range (−1 to 1), while the overall CVI demonstrated satisfactory agreement among experts regarding the relevance and appropriateness of the learning media. Expert evaluations further suggested that the SLBPE game has the potential to increase students’ learning motivation, improve classroom engagement, facilitate the acquisition of fundamental movement skills and health knowledge, and encourage the development of active and healthy lifestyle habits. Conclusion: The SLBPE game is a valid instructional medium for elementary Physical Education and represents a promising game-based learning resource for supporting physical literacy development. Its integration of cognitive, psychomotor, and affective learning components makes it suitable for creating more engaging, meaningful, and student-centred PE learning experiences.